2019
DOI: 10.1002/hpm.2741
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of beneficiaries, health service providers, and community members on a maternal and child health conditional cash transfer pilot programme in Nigeria

Abstract: Summary Background Our paper presents experiences and perceptions of beneficiaries, health service providers, and community members about a conditional cash transfer (CCT) programme piloted in Nigeria from April 2013 to May 2015 to boost demand for maternal, newborn, and child health services. Methods We conducted a descriptive cross‐sectional retrospective study using both qualitative and quantitative methods. Personal interviews and focus group discussions (FGDs) were conducted between June and July 2015 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
2
0
0
Order By: Relevance
“…Additionally, we found that CCT was a financial aid for establishing petty businesses and solving personal problems outside what it was intended for. Our study agrees with previous studies which averred that CCT was used in addressing poverty as beneficiaries indicated that they utilized the money in establishing businesses (40,48). This is not a surprise as 40.1% of the total population of Nigeria were categorized as being poor and has actual per capita expenditure less than N137,430($381) per year (49).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, we found that CCT was a financial aid for establishing petty businesses and solving personal problems outside what it was intended for. Our study agrees with previous studies which averred that CCT was used in addressing poverty as beneficiaries indicated that they utilized the money in establishing businesses (40,48). This is not a surprise as 40.1% of the total population of Nigeria were categorized as being poor and has actual per capita expenditure less than N137,430($381) per year (49).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding is in consistence with a systematic review on the impact of CCT on Maternal and Newborn Health in Kenya, Malawi, India, Nepal, Uruguay, Cambodia, and South Africa which showed a significant increase in the utilization of different MCH service (prenatal monitoring, ANCs, facility deliveries and, immunization) ( 22 , 28 , 39 ) among the target population. A similar study in Nigeria corroborated with our study showing a significant increase in more women attending four or more ANC visits, facility birth, and receiving two or more tetanus toxoid doses during pregnancy ( 28 , 40 ). In the context of other healthcare preventive and curative services, CCT had been previously reported to improve: HIV testing, care, and prevention ( 13 , 41 ); completion of tuberculosis treatment regimens ( 42 , 43 ); adherence to the hepatitis B vaccine ( 44 ) and; nutritional uptake ( 45 ).…”
Section: Discussionsupporting
confidence: 90%